2017
DOI: 10.1038/s41598-017-12094-z
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in overweight and obesity among urban children and adolescents, 2003–2012: A serial cross-sectional study in Guangzhou, China

Abstract: Childhood and adolescent overweight and obesity are increasing in China, but limited information is available on its secular trends in Guangzhou. In this cross-sectional study, ten-wave successive data were obtained from the physical fitness surveillance for students in Guangzhou from 2003 to 2012. A total of 2,619,154 urban students aged 7–18 years were included. The age-standardized prevalence of overweight and obesity increased significantly over the period: overweight rose from 10.15% to 14.07% in boys and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
0
15
0
2
Order By: Relevance
“…Although genetic factor plays an important role in obesity, the environmental and lifestyle factors such as physical activity and nutrition patterns are also considered to be of major importance [17]. Studies suggested that this increase could be attributed to rapid change of dietary and physical activity patterns [18].…”
Section: Discussionmentioning
confidence: 99%
“…Although genetic factor plays an important role in obesity, the environmental and lifestyle factors such as physical activity and nutrition patterns are also considered to be of major importance [17]. Studies suggested that this increase could be attributed to rapid change of dietary and physical activity patterns [18].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing secular trends regarding body mass can be observed even in the youngest age groups (Olds, ; Sedlak, Pařízková, Daniš, Dvořáková & Vignerová, ). Furthermore, in many countries, including Poland, we observe a halt in the positive secular trend for body height, while there is still an increasing secular trend for body weight, resulting in the significant intergenerational growth in BMI (Freedman et al, ; Kryst et al, ; Sanna & Soro, ; Topçu, Orhon, Ulukol & Başkan, ; Zong et al, ).…”
Section: Introductionmentioning
confidence: 88%
“…Obesity increases at an alarming rate in the world's population, including the Chinese communities. [1][2][3] It is estimated that 150 million adults and 15 million children are obese, and almost 30.4 million overweight or obese children and adolescents of China in 2010. 4 Some studies show increasing of obesity incidents in China, owing to rapid economic development and dramatic transitions in lifestyle of Chinese populations.…”
Section: Introductionmentioning
confidence: 99%
“…4 Some studies show increasing of obesity incidents in China, owing to rapid economic development and dramatic transitions in lifestyle of Chinese populations. [1][2][3]5 However, its cure has remained mostly ineffective, followed by the poor physical activities among students which reported causing numerous health problems, such as damaged lung function in children and adolescents. 6 Lately, obesity reports cause a significant change in the respiratory system, resulting in loss on thoracoabdominal synchronism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation